METODE INPUTING DATA SISTEM INFORMASI PEMINJAMAN LABORATORIUM TEKNIK ELEKTRONIKA POLITEKNIK NEGERI MALANG - Imam Saukani Saukani; Eko Pamuji (Politeknik Negeri Malang, 2020)
This research report is a response to address the deficiencies in the lending system in laboratory instrumentation that is, the lending system is still done manually. The definition of a student loan to manually write the name, code and the number of tools that will be borrowed and submit the Student Identity Card (KTM) as collateral. Such borrowing procedure causes the system to become less effective ministry. In this Research Report, applications are made to the database in the laboratory identification using barcode technology. This application is created using ms access 2003 software for the database. The main function of this application is to simulate the process of borrowing and repayment instrumentation. The process was carried out through scanning the barcode on the card members (KTM) and instrumentation devices using barcode scanner. After the whole simulation process is complete, the data is stored in a database and can be printed to be used as evidence of borrowing. Other functions include, process data search've borrowed, instrumentation load, as well as lending report.